Antidepressants in paediatric depression: do not look back in anger but around in awareness. (30th January 2018) - Brent, David A.; Gibbons, Robert D.; Wilkinson, Paul; Dubicka, Bernadka
Abstract : Summary: In this paper, we summarise and critique a network meta-analysis (NMA) of antidepressant efficacy and tolerability for paediatric depression and an accompanying editorial. Although we agree that many of the extant studies are flawed, this meta-analysis showed clear efficacy of fluoxetine in the NMA, and for sertraline and escitalopram in pairwise analyses. Consequently, these papers underestimate the benefits of antidepressants for paediatric depression, and provide support for current practice guideline, which recommends the use of an antidepressant if the patient does not respond to psychotherapy. In these circumstances, fluoxetine should be the first choice, with escitalopram and sertraline as alternatives. Declaration of interest: D.A.B. receives royalties from Guilford Press, has or will receive royalties from the electronic self-rated version of the C-SSRS from eResearch Technology, Inc., is on the editorial board of UpToDate, and is a reviewer for Healthwise. R.D.G. serves as an expert witness for the US Department of Justice, Pfizer, Wyeth and GSK; and is the founder of Adaptive Testing Technologies. P.W. receives personal fees from Lundbeck and Takeda. B.D. reports a licensing agreement with Lundbeck for a psychosocial treatment manual for depression. No other disclosures were reported.